2013
DOI: 10.1016/j.soard.2011.09.027
|View full text |Cite
|
Sign up to set email alerts
|

Omentectomy added to Roux-en-Y gastric bypass surgery: a randomized, controlled trial

Abstract: BACKGROUND Visceral adipose tissue (VAT) predicts incipient diabetes mellitus and cardiovascular disease. Human data is mixed regarding the benefits of selective VAT reduction. OBJECTIVES We investigated omentectomy added to laparoscopic Roux-en-Y gastric bypass (LRYGB) on glucose homeostasis and lipids, inflammatory markers and adipokines after 90-days in non-diabetic patients. SETTING Legacy Good Samaritan Hospital and Oregon Health & Science University in Portland, Oregon. METHODS A single-blinded, ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(24 citation statements)
references
References 32 publications
(49 reference statements)
2
20
0
2
Order By: Relevance
“…There are some reports of surgical removal of visceral fat thorough omentectomy [25,26]. There was no significant difference between RY gastric bypass without omentectomy and with omentectomy in fat mass 12 months after surgery [25]; this is compatible with our result.…”
Section: Discussionsupporting
confidence: 91%
“…There are some reports of surgical removal of visceral fat thorough omentectomy [25,26]. There was no significant difference between RY gastric bypass without omentectomy and with omentectomy in fat mass 12 months after surgery [25]; this is compatible with our result.…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, a study of weight loss induced by diet/lifestyle intervention showed that a reduction in visceral but not subcutaneous fat mass correlated with metabolic improvement (6). On the other hand, several studies have shown that removal of a subset of visceral adipose tissue (the greater omentum) in connection with bariatric surgery does not cause additional improvements in the metabolic profile (7)(8)(9).…”
Section: Discussionmentioning
confidence: 99%
“…When changes in body composition were compared after malabsorptive biliointestinal bypass (BIBP) and restrictive LAGB during a 4-year follow-up, the effects of BIBP were greater on total fat loss and trunk fat 49 . When omentectomy accompanies a laparoscopic Roux-en-Y gastric bypass (RYGB) procedure, changes in glucose homeostasis, lipid levels, and adipokine profile at 90 days postoperatively have been variably reported 50,51 .…”
Section: Expected Benefit On Cvd Risk Factorsmentioning
confidence: 99%